2002
DOI: 10.1097/00005131-200207000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Pertrochanteric Fractures: Is There an Advantage to an Intramedullary Nail?

Abstract: There is no advantage to an intramedullary nail versus a sliding compression hip screw for low-energy pertrochanteric fractures AO/OTA 31-A1 and A2, specifically with its increased cost and lack of evidence to show decreased complications or improved patient outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
70
1
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 274 publications
(78 citation statements)
references
References 31 publications
6
70
1
1
Order By: Relevance
“…18 In line with our results, 87 (51.8%) of the patients lived at home, but the authors did not report the number of patients who were able to walk independently. Although the mean pre-and post-operative scores of function and mobility did not differ significantly between the treatment groups, there was an increase by a factor of 1.5 in the score for social function during follow-up in the PFN group compared with the DHS group.…”
Section: Discussionsupporting
confidence: 76%
“…18 In line with our results, 87 (51.8%) of the patients lived at home, but the authors did not report the number of patients who were able to walk independently. Although the mean pre-and post-operative scores of function and mobility did not differ significantly between the treatment groups, there was an increase by a factor of 1.5 in the score for social function during follow-up in the PFN group compared with the DHS group.…”
Section: Discussionsupporting
confidence: 76%
“…In our study, the mean age of the patient was 69.17 years and the highest incidence (33.33%) of injury was seen among the age group of 70 to 80 due to poor vision, osteoporotic bone quality, menopausal ladies, slippery mud and negligence by the family members as noted by history. Various studies also showed mean age more than 60 years [11][12][13][14] . Around 58% patients were male and 42% were female.…”
Section: Discussionmentioning
confidence: 97%
“…11 In 2002, Saudan M and Sadowski C performed a randomized prospective study of 206 patients comparing dynamic hip screw and proximal femoral nail and stated the advantages of an intramedullary nail. 12 In 2002, Al Yassari G, Jones JW, Al Lami M published the advantages of the AO proximal femoral nail for the treatment of unstable trochanteric fractures. 13 In 2004, Schipper IB, Steyerberg EW and Kerver AJH did a randomized comparison of the gamma nail and proximal femoral nail of 424 cases.…”
Section: Review Of Literaturementioning
confidence: 99%